2018
DOI: 10.1371/journal.pone.0196697
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-425 and microRNA-155 cooperatively regulate atrial natriuretic peptide expression and cGMP production

Abstract: AimsAtrial natriuretic peptide (ANP), secreted primarily by atrial cardiomyocytes, decreases blood pressure by raising cyclic 3’,5’-guanosine monophosphate (cGMP) levels and inducing vasorelaxation, natriuresis, and diuresis. Raising the level of ANP has been shown to be an effective treatment for hypertension. To advance the future development of an anti-microRNA (miR) approach to increasing expression of ANP, we investigated the regulation of NPPA expression by two miRs: miR-425 and miR-155. We examined whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…Micro-RNA 425 and/or 155 (mir425 and/or mir155), which downregulate ANP gene expression and production, may be elevated in HF. 66 , 67 Moreover, Celik et al . 68 reported a cis -acting ANP antisense transcript (ANP-AS), negatively regulating ANP expression in human cardiomyocytes, which was increased in heart tissue of patients with advanced HF.…”
Section: Differential Regulation Of Anp and Bnp In Heart Failure And ...mentioning
confidence: 99%
“…Micro-RNA 425 and/or 155 (mir425 and/or mir155), which downregulate ANP gene expression and production, may be elevated in HF. 66 , 67 Moreover, Celik et al . 68 reported a cis -acting ANP antisense transcript (ANP-AS), negatively regulating ANP expression in human cardiomyocytes, which was increased in heart tissue of patients with advanced HF.…”
Section: Differential Regulation Of Anp and Bnp In Heart Failure And ...mentioning
confidence: 99%
“…The deletion of carboxyl-terminus regions of GC-A/NPRA suggested that the specific sequence in catalytic GCCD and protein-KHD played a pivotal role in the internalization, sequestration, and metabolic degradation of the receptor protein ( Pandey et al, 2000 ; Pandey, 2015 ). Interestingly, several studies have indicated that micro-RNA (miR) plays critical roles in the regulatory mechanisms and function of ANP/NPRA system ( Arora et al, 2013 ; Somanna et al, 2013 ; Wu et al, 2016 ; Vandenwijngaert et al, 2018 ; Khurana et al, 2022 ). Our recent findings have suggested that prolonged ANP treatments along with miR-128 and miR195 of cultured cells expressing high density of GC-A/NPRA caused downregulation of the receptor in a time-and dose-dependent manner ( Khurana et al, 2022 ).…”
Section: Endocytosis Intracellular Trafficking and Downregulation Of ...mentioning
confidence: 99%
“…Аллели, связанные с повышенными концентрациями НУП, также были связаны с более низким кровяным давлением и снижением вероятности развития АГ [23]. Недавно было показано, что микроРНК (miR-425) отрицательно регулирует продукцию ANP, а распространенный генетический вариант делает продукцию ANP устойчивой к miR-425 [24]. В исследовании у афроамериканцев циркулирующие концентрации NT-proBNP после поправки на клинические ковариаты были на 40% ниже, чем у представителей европеоидной расы, что может быть частично связано с генетической изменчивостью [25].…”
Section: современные сведения о роли Bnp и Nt-probnp в патогенезе рагunclassified